Molecular characterization of carbapenem resistance mechanisms and phenotypic correlations in clinical Klebsiella pneumoniae isolates from Ningbo, China - Qiu, Xuedan; Jiang, Min; Xu, Jianqiang; Wu, Qiaoping; Lin, Chenyao; Li, Weiying; Li, Qingcao (Frontiers in Microbiology, 2025)
ObjectiveThe purpose of this study is to understand the antimicrobial susceptibility and molecular distribution characteristics of carbapenem-resistant Klebsiella pneumoniae (CRKP) in the region, and to evaluate their correlation. Additionally, the study aims to investigate the transmission status of these strains.MethodsA total of 150 CRKP collected from January 2019 to December 2021 in the Ningbo region were included in this study. Antimicrobial susceptibility testing was performed using broth microdilution method following CLSI guidelines (CLSI, 2023). The tested agents included: (1) basic antimicrobials (tigecycline, polymyxin B, ceftazidime-avibactam); and (2) combination therapy candidates (ertapenem, imipenem, levofloxacin, piperacillin-tazobactam, ceftriaxone, cefepime, trimethoprim-sulfamethoxazole, fosfomycin, amikacin, aztreonam, chloramphenicol, amoxicillin-clavulanate, ceftazidime). Resistance genes were detected using polymerase chain reaction (PCR). Multi-locus sequence typing (MLST) was employed to analyze the molecular characteristics and evolutionary trends of the strains to determine their clonal relationships.ResultsThe 150 strains of CRKP exhibit high resistance rates to various conventional drugs; The sensitivity rates to tigecycline, polymyxin B, and ceftazidime-avibactam were 98.7, 98.0, and 68%, respectively; Conversely, the sensitivity rates to fosfomycin, amikacin, and chloramphenicol were 72.0, 40.0, and 16.7%, respectively; The main proportions of carbapemen genes producing in CRKP are as follows: KPC-2 (61.3%), NDM-5 (14.7%), IMP-4 (8.0%), OXA-232 (6.0%), and OXA-181 (1.3%); The main proportions of β-lactamase resistance genes are as follows: CTX-M-1 (13.33%), CTX-M-3 (25.33%), CTX-M-9 (17.33%), CTX-M-14 (34.67%), SHV-1 (26.66%), SHV-11 (66.66%), SHV-12 (18.66%), and SHV-28 (10.00%); CRKP carrying class A, B, and D carbapenemases had a sensitivity rate greater than 96% for tigecycline and polymyxin B, while their sensitivities to ceftazidime-avibactam, aztreonam, and amikacin varied significantly (p < 0.01). Analysis of the MLST results for CRKP revealed that ST11 strains were predominant in the region. There was a significant difference in the resistance genes carried by ST11 strains compared to non-ST11 strains. While different healthcare institutions exhibited variations in ST types, the strains generally showed high homogeneity.ConclusionIn the region, CRKP showed high sensitivity to tigecycline, polymyxin B, ceftazidime-avibactam, fosfomycin, amikacin, and chloramphenicol. The main carbapenemase genes identified were KPC-2 and NDM-5. The inhibitory effects of ceftazidime-avibactam, aztreonam, and amikacin varied for CRKP carrying different enzyme types. ST11 strains were predominant in the region. There was a significant difference in the resistance genes carried by ST11 strains compared to non-ST11 strains. Clonal dissemination was observed both within the same healthcare institution and between different institutions.